(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: In recent years investigations looked at pregnant women in Enugu, Nigeria, and Jeddah, Saudi Arabia, to see how much they knew about venous thromboembolism (VTE). Research showed a lack of understanding of VTE. In Enugu, 40% had heard of VTE, 30% had looked up information online while pregnant, and 20% were unaware of any symptoms. Adult Saudi women were aware of VTE in pregnancy but were unaware of risk factors and complications. VTE, which involves clot migration and puts expectant mothers at risk, frequently results in ICU admissions. The study aimed to assess pregnancy related VTE awareness among medical students in Saudi Arabia. Methods: The study design was cross-sectional research on Saudi adult females, including medical students up to the fifth year. The study contained medical students from the first to fifth year and sixth-year Saudi interns, with 2023's final quarter enrolling pregnant women from various Saudi provinces. This research highlights insufficient VTE awareness, particularly among pregnant women and medical students, advocating for enhanced awareness initiatives and education. Results: As regard the knowledge and awareness score about VTE during pregnancy, there were (66.9%) out of 498 participants exhibited a moderate level of knowledge on this critical health concern, which is an encouraging finding. However, there was a significant proportion (9.6%) with a low level of knowledge. Notably, the high level of knowledge observed in 23.5% of the participants. Regarding the relation between knowledge level and sociodemographic characteristics, there was a statistically significant relation to gender (p value=0.001), age (p value=0.001), social status (p value=0.0001), region of residence (p value=0.0001). It also shows statistically insignificant relation to nationality. Conclusion: the study highlighted a concerning gap in awareness and knowledge regarding venous thromboembolism (VTE) in pregnant women among medical students in Saudi Arabia. While approximately 66.9% of participants demonstrated a moderate level of understanding, a significant number—9.6%—displayed low awareness, emphasizing the need for improved education and training on this critical health issue. The findings reveal that many individuals struggle to identify risk factors and symptoms associated with VTE, which could lead to serious health consequences for both mothers and their infants.